2022
DOI: 10.14245/ns.2244156.078
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in the Surgical Management of Intramedullary Tumors: A Multicenter Study of 1,033 Patients by the Neurospinal Society of Japan

Abstract: Objective: We performed a retrospective observational study to demonstrate the surgical risks and long-term prognoses of intramedullary tumors in Japan using a multicenter registry authorized by the Neurospinal Society of Japan.Methods: Data from 1,033 consecutive patients with intramedullary tumors, treated between 2009 and 2020, were collected from 58 centers. Patients with spinal lipomas or myxopapillary ependymomas were excluded. Patient characteristics, clinical presentations, imaging characteristics, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Owing to these reasons, it is possible that PDT has not been recognized as a treatment option by physicians who usually treat malignant the spinal cord tumors. In fact, according to a recent report from Japan of 1033 cases of intramedullary spinal cord tumors in the previous 12 years [ 12 ], there were only 29 cases (2.8%) of tumors demonstrating a malignant histology including WHO grades 3 or 4. Furthermore, in a study of 48 cases during 7 years from France [ 13 ], there were only 3 cases (6.3%) of tumors demonstrating malignant histology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to these reasons, it is possible that PDT has not been recognized as a treatment option by physicians who usually treat malignant the spinal cord tumors. In fact, according to a recent report from Japan of 1033 cases of intramedullary spinal cord tumors in the previous 12 years [ 12 ], there were only 29 cases (2.8%) of tumors demonstrating a malignant histology including WHO grades 3 or 4. Furthermore, in a study of 48 cases during 7 years from France [ 13 ], there were only 3 cases (6.3%) of tumors demonstrating malignant histology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study of 48 cases during 7 years from France [ 13 ], there were only 3 cases (6.3%) of tumors demonstrating malignant histology. Among Japanese cases, after surgery, the adjuvant radiotherapy was performed on 130 patients (12.6%) including those with grade 2 ependymomas, and temozolomide-based chemotherapy was performed on 81 patients (7.8%) [ 12 ], however, no other types of treatment were performed in this previous Japanese study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Approximately 70% of PSCTs are reported to be benign or unknown, 3 suggesting that most PSCTs can be cured by total resection. 4 Postoperative worsening of neurological symptoms is not common in PSCTs, which has been reported to be 2.2%. 5 However, the removal of PSCTs, especially intramedullary tumors that originate in the spinal cord, inevitably involves invasion of normal nerve tissues, and the procedure requires a sensitive technique based on extensive experience.…”
Section: Introductionmentioning
confidence: 97%
“…PSCTs arise from the meninges, spinal cord, and cauda equina, with annual incidence of 0.35, 0.59, and 0.03 per 100,000 persons, respectively [ 2 ]. Approximately 70% of PSCTs are reported to be benign or unknown [ 3 ], suggesting that most PSCTs can be cured by total resection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we reported our experience with LIMSCTs, which has rarely been discussed separately in previous literature. 8,9 Based on a series of 43 patients treated in our institution, we analyzed the tumor characteristics, extent of resection and clinical outcomes and attempted to provide answers on optimal treatment strategies for LIMSCTs.…”
Section: Introductionmentioning
confidence: 99%